Changes in Blood Cell Deformability in Chorea-Acanthocytosis and Effects of Treatment With Dasatinib or Lithium - Reichel, Felix; Kräter, Martin; Peikert, Kevin; Glaß, Hannes; Rosendahl, Philipp; Herbig, Maik; Rivera Prieto, Alejandro; Kihm, Alexander; Bosman, Giel; Kaestner, Lars; Hermann, Andreas; Guck, Jochen (Frontiers in Physiology, 2022)
Misshaped red blood cells (RBCs), characterized by thorn-like protrusions known as acanthocytes, are a key diagnostic feature in Chorea-Acanthocytosis (ChAc), a rare neurodegenerative disorder. The altered RBC morphology likely influences their biomechanical properties which are crucial for the cells to pass the microvasculature. Here, we investigated blood cell deformability of 5 ChAc patients compared to healthy controls during up to one-year individual off-label treatment with the tyrosine kinases inhibitor dasatinib or several weeks with lithium. Measurements with two microfluidic techniques allowed us to assess RBC deformability under different shear stresses. Furthermore, we characterized leukocyte stiffness at high shear stresses. The results show that blood cell deformability – including both RBCs and leukocytes - in general is altered in ChAc patients compared to healthy donors. Therefore, this study shows for the first time an impairment of leukocyte properties in ChAc. During treatment with dasatinib or lithium, we observe alterations in RBC deformability and a stiffness increase for leukocytes. The hematological phenotype of ChAc patients hints at a reorganization of the cytoskeleton in blood cells which partly explains the altered mechanical properties observed here. These findings highlight the need for a systematic assessment of the contribution of impaired blood cell mechanics to the clinical manifestation of ChAc.